Understanding Geospatial Intelligence and the Challenges of Effective Counter-Terrorism Strategy: A Case Study of Nigeria's Boko Haram Challenge - Ngboawaji Daniel Nte; Baba Ahmadu Abdulaziz; Michael Uzorka (Universitas Negeri Semarang, 2020)
Nigeria is faced with a number of security challenges that have threatened the existence of peace and security in the country. These threats to public safety and national security have greatly undermined the government primary responsibility of guaranteeing public safety and national security. The intractable challenges posed by Boko Haram makes a good case for the above assertion. This work, therefore reviews the applicability of Geospatial Intelligence and all its components and sub-field, with a view to understanding and or establishing their respective relevance in devising effective counter-terrorism strategies in Nigeria. This was done, taking Boko Haram activities between 2015 and 2018 for specific study, against the background of Geospatial Intelligence capabilities .The researchers utilised primary and secondary data sources in this work. The Primary data sources was from questionnaires administered physically and electronically via emails while Secondary data came from published books, journals, articles, lecture guides, videos etc. Acquired data was statistically analysed using simple percentage and Chi-Square statistics. Sequel to the statistical results, findings were made that Geospatial-Intelligence is relevant and remains the most potent frontier in developing effective counter-terrorism strategies against Boko Haram and indeed other similar insurgencies in Nigeria.